Report from MDE practice: An interview-based evaluation of model-driven engineering uses - Hessa Alfraihi; Kevin Lano (PLoS ONE, 2025)
In this study, we investigate the usability of Model-Driven Engineering (MDE) through interviews with fifteen practitioners from diverse roles (e.g., developers, researchers, architects) and domains, and with a range of expertise levels across academic and industrial software sectors, capturing in-depth perspectives on its practical application. Participants emphasized MDE’s benefits in enhancing project robustness, reliability, development speed, and system organization. However, they also identified challenges such as a steep learning curve, technological constraints, organizational resistance, and a shortage of skilled professionals. To address these issues, participants recommended simplifying tools and language, improving consistency and flexibility, enhancing integration with existing workflows, and raising awareness of MDE. These insights provide valuable guidance for improving MDE usability and encouraging broader MDE adoption.